Detection and characterization of viruses of the genus Megalocytivirus in ornamental fish imported into an Australian border quarantine premises: an emerging risk to national biosecurity. Issue 2 (30th January 2014) - Nolan, D; Stephens, F; Crockford, M; Jones, J B; Snow, M
Abstract This report documents an emerging trend of identification of Megalocytivirus‐like inclusions in a range of ornamental fish species intercepted during quarantine detention at the Australian border. From September 2012 to February 2013, 5 species of fish that had suffered mortality levels in excess of 25% whilst in the post‐entry quarantine and had Megalocytivirus‐like inclusion bodies in histological sections were examined by PCR. The fish had been imported from Singapore, Malaysia and Sri Lanka. Ninety‐seven of 111 individual fish from affected tanks of fish tested were positive for the presence of Megalocytivirus by PCR. Sequence analysis of representative PCR products revealed an identical sequence of 621 bp in all cases which was identical to a previously characterized Megalocytivirus (Sabah/RAA1/2012 strain BMGIV48). Phylogenetic analysis of available Megalocytivirus major capsid protein (MCP) sequences confirmed the existence of 3 major clades of Megalocytivirus. The virus detected in this study was identified as a member of Genotype II. The broad host range and pathogenicity of megalocytiviruses, coupled to the documented spread of ornamental fish into the environment, render this a significant and emerging biosecurity threat to Australia.